Evaluating Governance, Risk, and Control in APIP Capability: A Case of Regency X Inspectorate - Ainun Putri; Dyah Setyaningrum (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
The 2023–2024 APIP Capability Assessment showed that the Inspectorate of Regency X achieved Level 3, indicating progress in GRC assurance components. However, BPKP’s evaluation of SPIP maturity, representing GRC assurance, revealed a decline. This study investigates this inconsistency by evaluating the implementation of governance, risk, and control (GRC) in the Inspectorate of Regency X based on BPKP Regulation No. 8 of 2021. A qualitative method was applied through document review and interviews, analyzed using content and thematic analysis. The findings show that GRC implementation is not fully aligned with regulatory stages, with eight stages achieved and eight partially fulfilled. Four major themes emerged: the role of BPKP, understanding among regional apparatus organizations, risk registers, and working instruments. The study concludes that while APIP capability shows improvement, it is not yet fully reflected in GRC implementation, emphasizing the need for stronger integration between assurance and governance mechanisms. Keywords : GRC; APIP Capability; Evaluation